2022
DOI: 10.1136/bmjopen-2021-052227
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to implementation of non-medical independent prescribing in primary care in the UK: a qualitative systematic review

Abstract: ObjectivesTo support workforce deficits and rising demand for medicines, independent prescribing (IP) by nurses, pharmacists and allied health professionals is a key component of workforce transformation in UK healthcare. This systematic review of qualitative research studies used a thematic synthesis approach to explore stakeholders’ views on IP in primary care and identify barriers and facilitators influencing implementation.SettingUK primary/community care.ParticipantsInclusion criteria were UK qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 145 publications
1
17
0
Order By: Relevance
“…In terms of perceived facilitators, the Delphi study highlighted ‘NP increases independence in the functions and responsibilities of the nursing profession’, ‘institutional support’, ‘adaptation to new roles and tasks of the nursing profession’, followed by ‘NP favors the autonomy of the nursing professional in the case of chronic care processes’ and ‘NP implies greater visualization and empowerment of the nursing collective within the care process’. These facilitators have also been recorded by other authors (Edwards et al., 2022; Fernández‐Ortega et al., 2016; McBrien, 2015), who concur that the nurse is key to optimal implementation of the prescription.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…In terms of perceived facilitators, the Delphi study highlighted ‘NP increases independence in the functions and responsibilities of the nursing profession’, ‘institutional support’, ‘adaptation to new roles and tasks of the nursing profession’, followed by ‘NP favors the autonomy of the nursing professional in the case of chronic care processes’ and ‘NP implies greater visualization and empowerment of the nursing collective within the care process’. These facilitators have also been recorded by other authors (Edwards et al., 2022; Fernández‐Ortega et al., 2016; McBrien, 2015), who concur that the nurse is key to optimal implementation of the prescription.…”
Section: Discussionsupporting
confidence: 59%
“…(2022) added that concerns about professional boundaries, if left unaddressed, can be divisive and prevent nurses from prescribing and should be carefully considered. The ‘lack of support, information and training by the institution/administration to the nursing staff’ is one of the barriers mentioned by several authors (Edwards et al., 2022; Fox et al., 2022; Naderi et al., 2021) who consider it an organizational‐institutional obstacle that restricts the extension of prescribing, identifying the impact of the NP policy as potentially enabling and/or restrictive. Despite this fact, nurses in Spain have seen the catalogue of medications to be prescribed recently expanded, beginning with treatments for wounds and burns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The NMP literature has largely focused on assessing the benefits and effectiveness of prescribing authorities without evaluating the costs and resource use. Some other studies have concentrated on topics such as NMP trends and related national policies over time or implementation barriers and/or facilitators of NMP for different professions 1 9 17 24 43. This review demonstrated the lack of evidence on costs, consequences and value for money in NMP by different groups of healthcare professionals.…”
Section: Discussionmentioning
confidence: 95%